Flow-T stenting with the Silk Vista Baby and Baby Leo stents for bifurcation aneurysms – A novel endovascular technique. Issue 1 (February 2020) - Makalanda, HLD; Wong, K; Bhogal, P
We present the first case using a novel flow diverter, the Silk Vista Baby (Balt, Montmorency, France), in combination with a low-profile braided stent, the Baby Leo (Balt, Montmorency, France), in a T configuration that we term Flow-T. We describe the technical characteristics of the case as well as the early follow-up results. We believe that this combination may provide an alternative to standard T-stenting and alternative to treat bifurcation aneurysms.